2014
DOI: 10.1007/s12663-014-0687-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orthognathic Surgery on the Posterior Airway Space in Patients Affected by Skeletal Class III Malocclusion

Abstract: Introduction Dentofacial deformity refers to deviations from normal facial proportions and dental relationships that are severe enough to be handicapping. These anomalies involve many aspects of patient's life and are sometimes also associated with a reduction of pharyngeal air space. Through orthognathic surgery it is possible to treat dentofacial deformities: this kind of surgery has several effects on skeletal structures and it has changes, as it is demonstrated by many studies, also on the upper airways. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…Maxillary advancement, through Le-Fort I osteotomy, with an average 5.5 mm (range of 3-7 mm) was performed for both group in our study and this was in accordance Chang et al (17) Santagata et al (18) Gokce et al (19) who found that the maxillary advancement lead to anterior movement of the soft palate with subsequent increase in volume of the airway. Chang et al (17) found that maxillary advancement of 7 mm might be adequate to increase the volume of the airway especially nasopharyngeal airway, while more than7 mm maxillary advancement will cause a decrease in airway volume "Plateau effect".…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Maxillary advancement, through Le-Fort I osteotomy, with an average 5.5 mm (range of 3-7 mm) was performed for both group in our study and this was in accordance Chang et al (17) Santagata et al (18) Gokce et al (19) who found that the maxillary advancement lead to anterior movement of the soft palate with subsequent increase in volume of the airway. Chang et al (17) found that maxillary advancement of 7 mm might be adequate to increase the volume of the airway especially nasopharyngeal airway, while more than7 mm maxillary advancement will cause a decrease in airway volume "Plateau effect".…”
Section: Discussionsupporting
confidence: 89%
“…Such new soft tissue relationships contribute to significant changes in the facial aesthetics and in the airway dimensions. (18)(19)(20)(21)(22)(23)(24) Accordingly, this retrospective study was designed to evaluate the volumetric, cross sectional surface area, and linear changes of the airway by using 3D cone beam computer tomography (CBCT) imaging after two different orthognathic surgeries in the Egyptian population.…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between the amount of mandibular setback and the decrease in the PAS was reported, and the low magnitude of mandibular posterior repositioning may explain the absence of significant changes in the PAS. [ 30 34 ] Our data showed that the posterior movement of the maxilla and the mandible narrowed the pharyngeal airway and reduction of pharyngeal airway might be related with the development of snoring or sleep apnea. The 7 subjects with postoperative snoring and OSA in our study may also have been influenced by a larger magnitude of maxillar or mandibular backward positioning.…”
Section: Discussionmentioning
confidence: 82%
“…Bimaxillary orthognathic surgery for correction of Class III malocclusion caused an increase of the total airway volume and improvement of polysomnography parameters [59]. Bimaxillary surgery rather than mandibular setback surgery should be used to correct a class III deformity and reduce the risk of obstructive sleep apnea; in fact, bimaxillary surgery may have less effect on the pharyngeal airway patency than mandibular setback surgery alone [60]. A recent study suggested that BSSO presents less change in the pharyngeal airway space after mandibular setback surgery compared to intraoral vertical ramus osteotomy.…”
Section: Postoperative Airway Problemmentioning
confidence: 99%